Protocol for assessing soybean antixenosis to Heliothis virescens - Eduardo, Wellington Ivo [UNESP]; Boiça Júnior, Arlindo Leal [UNESP]; de Moraes, Renato Franco Oliveira [UNESP]; de Souza, Bruno Henrique Sardinha; Louvandini, Helder; Barbosa, José Carlos [UNESP] (Wiley, 2020)
Larvae of Heliothis virescens (Fabricius) (Lepidoptera: Noctuidae) often infest soybean crops, Glycine max (L.) (Fabaceae), causing significant yield losses in important soybean-producing regions. The use of soybean varieties resistant to lepidopteran larvae is a major approach in soybean integrated pest management. However, standardization and optimization of bioassays that are used to screen genotypes for insect resistance are essential for high-throughput phenotyping. Methodologies for screening were assessed to determine the most effective method for discriminating levels of antixenosis to H. virescens in soybean plants. Feeding and oviposition preference assays were performed to determine optimal densities of larvae and adults, and optimal plant structures and growth stages for conducting assays. In addition, trichome densities, and fiber and lignin contents were quantified in plant structures of soybean cultivars differing in resistance. Resistance levels of cultivars were best differentiated using nine neonate larvae and two 6-day-old larvae, and by using young leaves of plants at the vegetative stage. This was likely due to the more pronounced differences in lignin and fiber contents in young leaves of vegetative-stage plants. Density of adult pairs, plant structure, and growth stage did not affect ability to distinguish differences in oviposition preference by H. virescens. Higher numbers of eggs were found on the leaves, which were the plant structures that exhibited the lowest trichome densities. The protocol developed in this work will benefit future evaluations of soybean genotypes for antixenosis against H. virescens.
Keywords: fiber; high-throughput phenotyping; integrated pest management; IPM; Lepidoptera; lignin; methodology for resistance tests; Noctuidae; plant resistance; screening, Glycine max; tobacco budworm; trichomes